Perceived barriers to healthy eating and adherence to dietary guidelines: Nationwide study. Issue 8 (August 2020) - de Mestral, Carlos; Khalatbari-Soltani, Saman; Stringhini, Silvia; Marques-Vidal, Pedro
Summary: Background: People report many barriers that prevent them from achieving a healthy diet. Whether perceived barriers are associated with dietary behavior remains unclear. Objective: To assess the association between barriers to healthy eating and adherence to the Swiss dietary guidelines. Methods: Cross-sectional data from the Swiss Health Survey 2012 (N = 15, 450; 53% women). Barriers included price, daily habits, taste, gluttony, lack of time, lack of willpower, limited options in restaurants, in supermarkets, no social support, and social opposition. The associations between barriers and adherence to Swiss dietary guidelines were assessed using multivariable logistic regression. Results: Daily habits (odds ratio; 95% confidence interval: 0.91; 0.85–0.98) and taste (0.85; 0.79–0.91) were associated with lower adherence to the guidelines for fruits, while price (1.13; 1.06–1.21) and limited options in restaurants (1.33; 1.23–1.45) and in supermarkets (1.18; 1.03–1.35) were associated with higher adherence. Taste was associated with lower adherence to the guidelines for vegetables (0.72; 0.66–0.78), while price (1.20; 1.11–1.30), gluttony (1.17; 1.04–1.31), social group opposition (1.48; 1.18–1.85) and limited options in restaurants (1.56; 1.42–1.72) and in supermarkets (1.25; 1.07–1.47) were associated with higher adherence. Daily habits (0.82; 0.75–0.90), time (0.86; 0.78–0.94), lack of willpower (0.78; 0.70–0.87), and gluttony (0.86; 0.76–0.98) were associated with lower adherence to the guidelines for fish, whereas price (1.09; 1.01–1.19), and limited options in restaurants (1.26; 1.14–1.39) and supermarkets (1.40; 1.20–1.63) were associated with higher adherence. Daily habits (0.89; 0.82–0.97), taste (0.66; 0.61–0.72), lack of willpower (0.84; 0.76–0.92) and gluttony (0.66; 0.58–0.75) were associated with lower adherence to the guidelines for meat. Time (0.88; 0.78–0.99) was associated with lower adherence to the guidelines for dairy, while gluttony (1.26; 1.09–1.46) was associated with higher adherence. Daily habits was associated with lower adherence (0.91; 0.85–0.97) to the guidelines for liquids, while limited options in restaurants was associated with higher adherence (1.12; 1.03–1.22). Conclusion: In the Swiss adult population, several self-reported barriers to healthy eating appear to hinder adherence to the dietary guidelines, while other commonly reported barriers are linked to higher adherence.